Strategi Digital Public Relations Aston Sidoarjo Hotel & Conference Center dalam Membangun Kesadaran Merek melalui Media Sosial - Rifqi Fawwaz Musyaffa; Mochammad Arkansyah; Anita Agustina Wulandari; Aulia Afniar Rahmawati; Ni Nyoman Padang Cakra Binaraesa Ratnasari; Edelweis Putri Prima (Jurnal Spektrum Komunikasi, 2026)
The development of digital media has transformed marketing communication and public relations patterns in the hospitality sector. Social media has become an effective platform for building relationships with consumers while also increasing brand awareness. This study aims to determine the Digital Public Relations strategy implemented by Aston Sidoarjo Hotel & Conference Center in building brand awareness through social media. The research employed a descriptive qualitative method with a case study approach. Data collection techniques included in-depth interviews, social media observations, and documentation. The research informants consisted of parties from Aston Sidoarjo City Hotel who actively use social media as a promotional and communication tool with consumers. The results showed that the Digital Public Relations strategy implemented by Aston Sidoarjo City Hotel includes the utilization of Instagram and TikTok as digital promotional media, the use of attractive visual content, active interaction with consumers through comments and direct messages, the use of customer testimonials, and product storytelling to enhance emotional closeness with audiences. These strategies were considered effective in increasing the brand awareness of Aston Sidoarjo City Hotel among the public, especially digital consumers. This study demonstrates that social media plays an important role in building the image and brand awareness of hotels in the digital era.